Answer:
The answer is "0.5".
Step-by-step explanation:
Given:
![\to \lim_{x\to 2} \frac{(\sqrt{(6-x)}-2)}{(\sqrt{(3-x)}-1)}\\\\ \to \lim_{x\to 2} \frac{\frac{d(\sqrt{(6-x)}-2)}{dx}}{\frac{(\sqrt{(3-x)}-1)}{dx}}\\\\](https://tex.z-dn.net/?f=%5Cto%20%5Clim_%7Bx%5Cto%202%7D%20%20%5Cfrac%7B%28%5Csqrt%7B%286-x%29%7D-2%29%7D%7B%28%5Csqrt%7B%283-x%29%7D-1%29%7D%5C%5C%5C%5C%20%5Cto%20%5Clim_%7Bx%5Cto%202%7D%20%20%5Cfrac%7B%5Cfrac%7Bd%28%5Csqrt%7B%286-x%29%7D-2%29%7D%7Bdx%7D%7D%7B%5Cfrac%7B%28%5Csqrt%7B%283-x%29%7D-1%29%7D%7Bdx%7D%7D%5C%5C%5C%5C)
![\to \lim_{x\to 2} \frac{\frac{-1}{2\sqrt{(6-x)} }}{\frac{-1}{2\sqrt{(3-x)}}}\\\\](https://tex.z-dn.net/?f=%5Cto%20%5Clim_%7Bx%5Cto%202%7D%20%5Cfrac%7B%5Cfrac%7B-1%7D%7B2%5Csqrt%7B%286-x%29%7D%20%7D%7D%7B%5Cfrac%7B-1%7D%7B2%5Csqrt%7B%283-x%29%7D%7D%7D%5C%5C%5C%5C)
![\to \lim_{x\to 2} \frac{\sqrt{3-x}}{\sqrt{6-x}}\\\\ \to \frac{\sqrt{3-2}}{\sqrt{6-2}}\\\\ \to \frac{\sqrt{1}} {\sqrt{4}}\\\\ \to \frac{1}{2}\\\\ \to 0.5](https://tex.z-dn.net/?f=%5Cto%20%5Clim_%7Bx%5Cto%202%7D%20%5Cfrac%7B%5Csqrt%7B3-x%7D%7D%7B%5Csqrt%7B6-x%7D%7D%5C%5C%5C%5C%20%5Cto%20%5Cfrac%7B%5Csqrt%7B3-2%7D%7D%7B%5Csqrt%7B6-2%7D%7D%5C%5C%5C%5C%20%5Cto%20%5Cfrac%7B%5Csqrt%7B1%7D%7D%20%7B%5Csqrt%7B4%7D%7D%5C%5C%5C%5C%20%5Cto%20%5Cfrac%7B1%7D%7B2%7D%5C%5C%5C%5C%20%5Cto%200.5)
Answer:
No
Step-by-step explanation:
First solve both equations:
1) 9x = 5x + 4
Simplifying
9x = 5x + 4
Reorder the terms:
9x = 4 + 5x
Solving
9x = 4 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
9x + -5x = 4 + 5x + -5x
Combine like terms: 9x + -5x = 4x
4x = 4 + 5x + -5x
Combine like terms: 5x + -5x = 0
4x = 4 + 0
4x = 4
Divide each side by '4'.
x = 1
Simplifying
x = 1
2) 14x = 4
14x = 4 (divide both sides by 14 to get x)
14x/14 = 4/14
x = 0.285714285714
As you can see, the value of x in the second equations is less than one, therefore making these algebraic equations not equivalent.
X - 0.17 = y
add 0.17 to both sides
x = y + 0.17
Answer:
6,000
Step-by-step explanation:
A square has four sides. Hope this helps you.